Komitmen Organisasi Sebagai Mediator Pengaruh Insentif dan Lingkungan Kerja terhadap Kinerja Karyawan PT Jurong Engineering Lestari (PT JEL) Jakarta - Antos Sriandi; Endah Winarti HS; Siti Hidayah; S.B. Handayani (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the phenomenon of suboptimal employee performance at PT Jurong Engineering Lestari (PT JEL) Jakarta. One factor suspected of influencing this situation is the provision of incentives and a work environment that is not fully supportive, as well as organizational commitment, which plays a mediating role in this relationship. Furthermore, previous research has shown varying findings regarding the influence of incentives and the work environment on employee performance. Therefore, the purpose of this study is to analyze the role of organizational commitment as a mediator in the relationship between incentives and the work environment on employee performance at PT JEL Jakarta. This study used a quantitative approach using a survey method. The population in this study was all employees of PT JEL Jakarta, totaling approximately 1,900. The research sample was determined at 110 respondents using a purposive random sampling technique, and 101 respondents were able to analyze the data. Data collection was conducted through questionnaires, while hypothesis testing was conducted using multiple linear regression analysis using SPSS. The results of the study indicate that: (1) incentives and the work environment simultaneously have a positive and significant effect on organizational commitment; (2) organizational commitment, incentives, and the work environment have a positive and significant influence on employee performance; and (3) organizational commitment has been shown to mediate the influence of incentives and the work environment on employee performance. These findings reinforce the importance of organizational commitment as an intermediary variable in improving employee performance. The implications of this study suggest that companies need to prioritize fair and appropriate incentive systems and create a conducive work environment that supports collaboration among employees. This will foster a strong commitment from employees to contribute optimally to achieving organizational goals.